(3ebGjjS GdYdGbGJ GdGQJHGWjIs - (3HhLeYI (B, (3MQjRjs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2018)
(3JfGhd gPG GdcJGH eLehYI ef GdehGVjY GdeObbI aj GdEMUGA GdGSJOdGdj hebGjjS GdYdGbI GdGQJHGWjI HTcd efSLe eY GdNWI GdJOQjSjI GdeYJeOI aj GdLGeYI GdLRGFQjI (B((3eaGgje GMUGFjI, GdeYGedGJ GdGQJHGWjI deJZjQjf ef GdeSJhi Gdcej hGdQJHj hGdGSej (B...(3, JMdjd GdGfMOGQ (B)(3, ceG bOeJ eYXe ebGjjS GdYdGbI Hjf GdeJZjQGJ HTcd eJSdSd heJOQL djJfGSH hGdbOQGJ GdeNJdaI ddWdHI(B.s
(3GdeQGLY U(B.156 (3GdLOGhd U(B.159s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdGSJOdGdjs